2009
DOI: 10.1021/ef801024s
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine in Solid Fuels Fired in Pulverized Fuel Boilers — Sources, Forms, Reactions, and Consequences: a Literature Review

Abstract: Because Foster Wheeler North America Corp. (hereinafter “Foster Wheeler”) is supplying and supporting pulverized fuel (PF) boilers producing steam with higher temperatures and pressures, increasing emphasis must be given to potential sources of corrosion and deposition. Further, because Foster Wheeler is developing projects involving cofiring of biomass fuels (e.g., wood waste, agricultural materials) with coals from a variety of sources, again corrosion and deposition must be thoroughly investigated. Chlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 38 publications
1
78
0
Order By: Relevance
“…About 90% of the coal power plants use these types of boilers for power generation [4,23]. Small proportion of wood, biomass and agricultural materials can also be used as fuel in pulverized fuel boilers [24].…”
Section: Boiler (Afbc) Pressurized Fluidized Bed Combustion Boiler (mentioning
confidence: 99%
See 1 more Smart Citation
“…About 90% of the coal power plants use these types of boilers for power generation [4,23]. Small proportion of wood, biomass and agricultural materials can also be used as fuel in pulverized fuel boilers [24].…”
Section: Boiler (Afbc) Pressurized Fluidized Bed Combustion Boiler (mentioning
confidence: 99%
“…Steam is generated when the hot flue gases flow outside the pipe due to convection. These hot gases transfer their heat to the water present in the tubes and come out with a lower temperature [24][25][26].…”
Section: Boiler (Afbc) Pressurized Fluidized Bed Combustion Boiler (mentioning
confidence: 99%
“…Tillman and others [65] note that the corrosion problems caused by biomass fuels generally arise from the chlorine and alkali metals (specifically K and Na) they contain. With the exception of wood and a handful of other fuel crops, biomass fuels contain significantly higher concentrations of chlorine than coal.…”
Section: Corrosives In Biomass Fuelsmentioning
confidence: 99%
“…With the exception of wood and a handful of other fuel crops, biomass fuels contain significantly higher concentrations of chlorine than coal. [65] Field crops, with the exception of nut shells, pits and switchgrass, contain more chlorine than woody materials. Tables of typical chlorine and moisture concentrations in 20 biomass fuels [66] showed that chlorine concentrations, expressed as lb/10 6 Btu, ranged from 0.012 for willow, poplar and almond shells to 0.894 for rice straw and 0.923 for corn stover.…”
Section: Corrosives In Biomass Fuelsmentioning
confidence: 99%
See 1 more Smart Citation